2010
DOI: 10.1074/jbc.m110.133157
|View full text |Cite
|
Sign up to set email alerts
|

Protein- and Metal-dependent Interactions of a Prominent Protein in Mussel Adhesive Plaques

Abstract: The adhesive plaques of Mytilus byssus are investigated increasingly to determine the molecular requirements for wet adhesion. Mfp-2 is the most abundant protein in the plaques, but little is known about its function. Analysis of Mfp-2 films using the surface forces apparatus detected no interaction between films or between a film and bare mica; however, addition of Ca 2؉ and Fe 3؉ induced significant reversible bridging (work of adhesion W ad ≈ 0.3 mJ/m 2 to 2.2 mJ/m 2 ) between two films at 0.35 M salinity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
224
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(242 citation statements)
references
References 39 publications
11
224
2
3
Order By: Relevance
“…23,36 Indeed, CD of mfp-2 in the far UV was almost identical to that of oxidized recombinant human EGF, 22 29,37 and can be disrupted by temperature or reduction of disulfides. SFA studies have independently shown that mfp-2 is Ca 2þ binding 7 and a partially Ca 2þ -bound form of mfp-2 was apparently used in the CD studies. Bound calcium on mfp-2 was not easily removed by chelation with excess EDTA at pH 5.5 but released with reduction of disulfide bonding [ Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23,36 Indeed, CD of mfp-2 in the far UV was almost identical to that of oxidized recombinant human EGF, 22 29,37 and can be disrupted by temperature or reduction of disulfides. SFA studies have independently shown that mfp-2 is Ca 2þ binding 7 and a partially Ca 2þ -bound form of mfp-2 was apparently used in the CD studies. Bound calcium on mfp-2 was not easily removed by chelation with excess EDTA at pH 5.5 but released with reduction of disulfide bonding [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies allow the estimation of the hydrodynamic radius of mfp-2 at 3-4 nm. 7 In contrast to mfp-1, mfp-2, although also a flexible molecular necklace, has larger (40-45-res long) structured EGF domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13,48] In addition, the 3,4-dihydroxyphenylalanine (DOPA)-rich proteins in the mussel byssal plaque, such as mfp-3 (20 mol% DOPA) and mfp-5 (28 mol% DOPA), coordinated with Fe 3+ , enable the plaque to adhere to rocks containing metal ions under water. [13,[49][50][51][52] In conclusion, mussel byssal displays multi functional features, such as self-healing and adhesion, with different types of metal coordination interactions.…”
Section: Interface Interactionsmentioning
confidence: 93%